The dynamics of policy change in dominant subsystems: Colorado, Oregon, and the politics of growth - Corwin, Margaret I., author; Davis, Sandra K., advisor (Colorado State University. Libraries, 2002)
The dynamics of sudden and major change in the output of long-stable policy monopolies has been studied for several decades. A variety of political scientists have sought to identify the crucial dynamics involved when this type of change occurs (Bosso. 1987; Baumgartner and Jones, 1993; Sabatier and Jenkins-Smith. 1993; and Thurber. 1991). This cumulative body of research has identified the key variables and their dynamic interactions that are indicative of imminent major policy shifts. This research builds on earlier works by elevating the policy entrepreneur to key variable status. The role of the policy entrepreneur in facilitating policy change has long been noted by political scientists (Kingdon. 1984; Mintrom and Vergari. 1996; Schneider, Teske and Mintrom, 1995). However, the relative importance of the entrepreneur in relation to the other key variables of policy change has not been systematically studied. This study draws from the work of Mintrom and Vergari, (1996) and Schneider. Teske and Mintrom (1995) who have crafted a model of public entrepreneurship modeled after the economic concept of the private entrepreneur. In Oregon, major change occurred in the state's land use planning system in the early 1970s. while Colorado, with similar dynamics, has been unable to enact change in state land use laws. Oregon's state land use planning system has subsequently been the driving force behind change in the state's overall philosophy and approach to transportation planning, which emphasizes a broad-based, multi-modal approach to the movement of people and goods. Colorado has remained firmly committed to a highways-only approach as the centerpiece of state transportation planning. This thesis examines the key variables of major policy change by comparing and contrasting the policy change that occurred in Oregon, with the lack of policy change in Colorado, in an effort to identify the key independent variables and their dynamic interaction. Findings suggest that the key difference is the emergence of successful policy entrepreneurs in Oregon who successfully facilitated policy change. In Colorado, entrepreneurs were observed, but none were successful. From these findings, a suggested typology of entrepreneurial strategies linked to degree and scope of change desired is suggested as the focus for future research.
Keywords: political science